The impact of hypertension on sexual functions among women - Ciechacka, Maria; Pawełko, Agnieszka; Bąk, Ewelina (Journal of Education, Health and Sport, 2025)
Introduction. Human sexuality is an important factor in personality development. It is usually a positive driving force in the human population, motivating people to establish contacts and interpersonal bonds. The "gold standard" for screening tests for sexual disorders in women is currently the Female Sexual Function Index (FSFI). Particularly focusing on patients with hypertension can bring significant results. Material and methods The study was conducted among 106 women, including 48 diagnosed with hypertension and 58 without hypertension. The diagnostic survey method was used in this study. The study was conducted using the Female Sexual Function Index (FSFI) questionnaire. Results Hypertension has been shown to have a negative impact on all 6 domains of the FSFI and its overall score. The most negative feelings concern the arousal domain, and the least negative feelings concern the pain domain. Conclusions: Among patients with hypertension, there is a negative impact of this disease on sexual aspects. Patients with hypertension require greater focus on educational activities aimed at maintaining good blood pressure control, regular visits and compliance with therapeutic recommendations.